First of all, I think you have a typo in the g(x) equation.
I am pretty sure you meant to type
g(x) = (1/3)x - 4/3
I do not like questions where a student has to find errors, so I will simply do the question the correct way
g(-3) = (1/3)(-3) - 4/3
= -1 - 4/3
= -3/3 - 4/3
= - 7/3
f(1) = 3(1) - 5
= 3 - 5
= -2
I am not exactly sure of what I'm supposed to do in the following question:
Describe and correct the error, given the functions f(x)=3x - 5 and g(x)=1/3 - 4/3.
The first equation is as follows:
g(-3)= 1/3 - 4/3 (3)
=1/3 - 4
= -3 2/3
The second equation is:
f(1)= 1/3 - 4/3(1)
=1/3 - 4/3
= -3/3
-1
It appears to me that they wrote the functions in the wrong order, but I honestly have no idea what they're asking me to do. Also, it looks like the equations are correct! I'm home-schooled and learning math on your own is easily the most difficult thing, so all help is most appreciated. You don't exactly have to solve the question for me or anything, just simplifying it in any way would help me out. Thank you for reading!
3 answers
Looking at the comment and the way she substituted, I thing
g(x) = 1/3 - (4/3)x
g(x) = 1/3 - (4/3)x
Haha, Steve is correct, I apologize for the guesswork. :/
It's g(x)= 1/3 -4/3x.
Going off the work Reiny did, I am still rather clueless, so considering it's only two problems, I guess I'll just have to do some guesswork myself. Thank you for the help, though!
It's g(x)= 1/3 -4/3x.
Going off the work Reiny did, I am still rather clueless, so considering it's only two problems, I guess I'll just have to do some guesswork myself. Thank you for the help, though!